SOSIALISASI TERAPI KOMPLEMENTER KOMPRES HANGAT JAHE MERAH PADA LANSIA UNTUK MENURUNKAN SKALA NYERI RHEUMATOID ARTHRITIS DI WILAYAH KERJA UPTD PUSKESMAS MUNJUL JAYA PURWAKARTA - H. Nelson Doloksaribu; Sherly, Sherly; Monica Mawarni (Bajang Institute, 2023)
Rheumatoid Arthritis is a systemic autoimmune disease in patients with joints of the hands and feet who experience joint inflammation, which causes swelling.Pain can cause damage to the joints, it is estimated that around 1.7 billion people experience problems in the musculoskeletal system and are expected to increasein the next 10 years. There are 35% of Rheumatoid Arthritis sufferers in Purwakarta Regency. This research uses a descriptive method. The researchsubject used 1 elderly person aged ≥55 years with Rheumatoid Arthritis pain. Thisstudy focuses on reducing the pain scale using the Numaric Rating Scale (NRS). This research took place at the Munjul Jaya Health Center UPTD. How to collect data starting from interviews, observation and documentation. This research was made in accordance with the journal Widya Arisandy (2023) which explained thatthere was a decrease in the pain scale in the elderly suffering from Rheumatoid Arthritis after compressing it for 5 days, using warm red ginger compresses for 15minutes. There was a decrease from the first day of the 5th day of the pain scale tothe fifth day of the pain scale of 1. The results of the study with warm compresses of red ginger which were carried out for 5 days and within 15 minutes every day for one respondent there was a decrease which was initially a scale of 5 and onthe last day it became a scale 3. From the results of research conducted by researchers in line with the journals taken and there was a decrease by doing warm red ginger compresses.